COMPARISON OF THE EFFECTIVENESS OF EPIDURAL AND SPINAL ANALGESIA IN FIRST PARTURIENT WOMEN - Cardoso , Rômulo Henrique da Silva (2024)
The aim of this study is to comprehensively compare the efficacy of epidural and spinal analgesia in relieving pain during labor in primiparous women. Methodology:  To achieve the proposed objective, we conducted a systematic literature review, consulting electronic databases such as PubMed, Scopus, and Web of Science. A combination of search terms was used. Only comparative studies, such as randomized controlled trials and cohort studies, that directly investigated the efficacy of epidural versus spinal analgesia in primiparous women were included. The methodological quality of the selected studies was assessed following specific guidelines and predefined criteria. Results:  After a thorough analysis of the included studies, we observed that both epidural and spinal analgesia were effective in relieving pain during labor in primiparous women. However, the results indicated that epidural analgesia may provide more complete and prolonged pain relief, while spinal analgesia tends to have a quicker onset of action. Additionally, both techniques were associated with acceptable rates of complications and adverse effects, although some differences were observed regarding safety profiles. Conclusion: Based on the results obtained, we conclude that both epidural and spinal analgesia are effective options for pain relief during labor in primiparous women. The choice between these techniques should be individualized, taking into consideration patient preferences, progression of labor, and specific characteristics of each technique. A detailed discussion between the patient and the medical team is essential to determine the best analgesic approach for each case.